2005
DOI: 10.1007/s00424-005-1490-7
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase inhibition promotes the transition from compensated hypertrophy to cardiac dilatation in rats

Abstract: The cellular signaling pathways responsible for the transition from compensated left ventricular hypertrophy (LVH) to LV dilatation (remodeling) and heart failure are unclear. As chronic administration of a beta-adrenoreceptor (beta-AR) agonist mediates the premature onset of cardiac remodeling without myocyte necrosis or myocardial dysfunction in LVH, we suggest that beta-AR activation is critical in promoting the transition from compensated LVH to cardiac dilatation. However, beta-AR mediated effects in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, sustained LVH usually leads to the deterioration of heart functions, such as a reduced FS accompanied by wall thinning and chamber dilation. Since LVH is considered to be an independent risk factor for heart failure, intensive efforts have been focused on elucidating the signaling pathways involved in LVH (Hardt and Sadoshima, 2004) and developing strategies to prevent the transition from LVH to heart failure (Anamourlis et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, sustained LVH usually leads to the deterioration of heart functions, such as a reduced FS accompanied by wall thinning and chamber dilation. Since LVH is considered to be an independent risk factor for heart failure, intensive efforts have been focused on elucidating the signaling pathways involved in LVH (Hardt and Sadoshima, 2004) and developing strategies to prevent the transition from LVH to heart failure (Anamourlis et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Because the NO receptor, NOsensitive guanylyl cyclase, plays a key role in the NO/cGMP signal-transduction cascade (Russwurm and Koesling, 2004), isolated and perfused guinea-pig hearts were pre-treated with 10 μM ODQ, a soluble guanylyl cyclase selective inhibitor (Isenberg et al, 2006), then without stopping 10 μM ODQ infusion, 5 μM vulgarenol was infused continuously at 0.3 mL/min. Due to the fact that cyclic nucleotides are degraded by phosphodiesterases, it was decided to investigate whether phosphodiesterase-3 selective inhibition by pentoxifylline (a highly specific type 3 phosphodiesterase inhibitor) (Anamourlis et al, 2006) could have a role in the observed pharmacological effect. In all experiments, CVR and cGMP production in the ventricular segments were evaluated.…”
Section: Assay Of Cgmp Content In Ventricular Tissue Samplesmentioning
confidence: 99%
“…The fundamental mechanisms responsible for the transition from compensated to decompensated cardiac hypertrophy are only partially defined (1,31). Many studies point to death of cardiomyocytes and changes in the cellular/molecular mechanisms regulating extracellular matrix composition and organization as the most relevant factors in the transition from compensatory hypertrophy to pump failure in experimental and human hypertension (1,10,12,19,23,30,34,40,42).…”
mentioning
confidence: 99%
“…The fundamental mechanisms responsible for the transition from compensated to decompensated cardiac hypertrophy are only partially defined (1,31). Many studies point to death of cardiomyocytes and changes in the cellular/molecular mechanisms regulating extracellular matrix composition and organization as the most relevant factors in the transition from compensatory hypertrophy to pump failure in experimental and human hypertension (1,10,12,19,23,30,34,40,42). It has been also suggested that the accumulation of cytoskeletal proteins, tubulin and desmin, probably counteracting the increased strain on the myocardium due to chronic pressure overload, as well as changes in intercalated disc proteins may lead to cytoskeletal stiffness and reduced intercellular communication resulting in contractile dysfunction before the transition to overt HF (18,31).…”
mentioning
confidence: 99%